P0133INCREASED INTRA-ABDOMINAL PRESSURE DURING LAPARASCOPIC PNEUMOPERITONEUM ENHANCES ALBUMINURIA VIA RENAL VENOUS CONGESTION, ILLUSTRATING PATHOPHYSIOLOGICAL ASPECTS OF HIGH OUTPUT PREECLAMPSIA. (6th June 2020) - Schoutteten, Melanie; Pauline, Dreesen; Vande Velde, Nele; Heylen, Line; Kaminski, Iris; De Moor, Bart; Malbrain, Manu; Gyselaers, Wilfried
Abstract: Background and Aims: Intra-abdominal hypertension (IAH) causes severe organ dysfunction. Our aim is to evaluate the effect of increased intra-abdominal pressure (IAP) on renal function, hypothesizing that venous congestion may increase proteinuria and fluid retention without endothelial dysfunction. Method: Three urine samples were collected from 32 non-pregnant women undergoing laparoscopic assisted vaginal hysterectomy (LAVH) and from 10 controls placed in Trendelenburg position for 60 minutes. Urine sampling was done before (PRE), during or immediately after (PER), and two hours after (POST) the procedure. Urinary albumin, protein and creatinine concentrations were measured in each sample, ratios were calculated and compared within and between groups. Results: During LAVH, the albumin/creatinine ratio (ACR) increased and persisted POST-procedure, which was not observed in controls. A positive correlation existed between the LAVH duration and the relative change in both ACR and protein/creatinine ratio (PCR) PER- and POST-procedure. Conclusion: Iatrogenic IAH increases urinary ACR and PCR in non-pregnant women via a process of venous congestion. This mechanism might explain the presentation of one specific subtype of late-onset preeclampsia, where no drop of maternal cardiac output is observed.